The aesthetics of the digital common assessing the emerging discourse on landscape value of the content community - Bimbao, Jose Antonio P. (College of Architecture, University of the Philippines Diliman, 2017)
In the age of rapid technological advances, social media engagement becomes the platform to better understand the perspectives of the public. This sociological adaptation trend becomes an important design challenge as digital disruption of social media continues to influence industries like transportation, advertising, and hospitality. It pressures the industries to adapt to the trend for survival in this information age, as consumers have created a paradigm shift from the traditional one-way reception of information to a dual role of generating and receiving content. In this light, digital disruption is expected to impact more industries, possibly Landscape Architecture. The research query revolves on the relevance of digital disruption in the field of Landscape Architecture It inquires on the new human actor, the digital commoner, and its rising role in the planning of more relevant public places. As an important query in this new digital commoner user concept, the research will take advantage of the emerging digital disruption trend by looking into the value of user-generated content, specifically from the content community Instagram, to develop user-based landscape data analysis method that will generate landscape design expressions and develop a new landscape vocabulary. By establishing the relationship of information, aesthetics, and social capital, the connection between social media and landscape design is linked together. The method of the thesis has three critical phases: (1) pre-big data, (2) big data mining, and (3) analysis. The study revealed that social media embeds within landscape patterns that reflect aesthetic values of users, reinforcing methods to extract the values and translate it to an aesthetic landscape vocabulary is crucial for the industry of landscape Architecture, putting the practice in a position to timely adapt to the digital disruption trend. Social media is embedded with landscape patterns that reflect aesthetic values of users. Developing a method to extract the values and translate it to an aesthetic landscape vocabulary is vital for the industry of Landscape Architecture, as it puts the practice in a position to timely adapt to the digital disruption trend.